2012
DOI: 10.3998/ark.5550190.0013.811
|View full text |Cite
|
Sign up to set email alerts
|

A practical synthesis of diethyl 1-[(alkylamino)(cyano)methyl]vinylphosphonates

Abstract: A simple, convenient and highly stereoselective synthesis of diethyl (E)-1-(bromomethyl)-2-cyanovinylphosphonate 4 is described. The product would be a useful substrate for the synthesis of diethyl 1-[(alkylamino)(cyano)methyl]vinylphosphonates 5 via allylic rearrangement S N 2 -type mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previously, we have reported a new synthetic route to the diethyl (E)-1-(bromomethyl)-2-cyanovinylphosphonate 1 39 and its application in the synthesis of new vinylphosphonates 40,41 . Following our interest in the synthesis of polyfunctionalized 1,3-dienes [42][43][44] , we have sought to investigate, in the present work, the transformation of allyl bromide 1 into 1,3-dienes and the conditions of their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have reported a new synthetic route to the diethyl (E)-1-(bromomethyl)-2-cyanovinylphosphonate 1 39 and its application in the synthesis of new vinylphosphonates 40,41 . Following our interest in the synthesis of polyfunctionalized 1,3-dienes [42][43][44] , we have sought to investigate, in the present work, the transformation of allyl bromide 1 into 1,3-dienes and the conditions of their preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its importance, it is still of interest to develop novel approaches for the efficient generation of functionalized allyl bromide 1 . In this regard, we have previously described a simple and stereoselective synthesis of diethyl ( E )-1-(bromomethyl)-2-cyanovinylphosphonate 2 [ 19 ], an activated alkene bearing three functional groups. We have also demonstrated that the latter can be used as an efficient electrophilic synthon for the synthesis of a new family of allylamines [ 19 ], enamines [ 20 ], and vinyl ether [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have previously described a simple and stereoselective synthesis of diethyl ( E )-1-(bromomethyl)-2-cyanovinylphosphonate 2 [ 19 ], an activated alkene bearing three functional groups. We have also demonstrated that the latter can be used as an efficient electrophilic synthon for the synthesis of a new family of allylamines [ 19 ], enamines [ 20 ], and vinyl ether [ 20 ]. Prompted by the versatility of allyl bromide 2 , we suggested that its reaction with a variety of phenols and Gilman reagents would be a very convenient way to prepare new substituted aryl vinyl ethers 3 and diethyl 1-[(alkyl)(cyano)methyl]vinylphosphonates 4 ( Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Continuing with our efforts directed toward the development of new methodologies for the synthesis of functionalized brominated derivatives, [19][20][21][22][23][24] we describe in this paper an efficient alternative for the preparation of a new family of allyl bromide (E)-4 and vinyl bromide (E)-5 from tetraethyl prop-2-ene-1,2-diyldiphosphonate 2 (Scheme 1) with complete stereoselectivity in favour of the E configuration starting from inexpensive reagents. Allyl bromide (E)-4 has been separated and then transformed in a one-step synthesis, to a new family of tetraethyl 1-(alkylamino)prop-2-ene-1,2-diyldiphosphonates 6.…”
Section: Introductionmentioning
confidence: 99%